Pengaruh Lingkungan Kerja dan Stres Kerja Terhadap Kinerja Karyawan pada Kantor Operasional Jakarta PT. Asuransi Jiwa Inhealth Indonesia - Anita Carolina Gudi; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
This study aims to examine the effect of work environment and work stress on employee performance at the Jakarta Operational Office of PT. Asuransi Jiwa Inhealth Indonesia. The sampling technique used is saturated non-probability sampling, with the number of respondents as many as 60 employees. This research uses quantitative methods. The method of collecting data using a questionnaire. The analysis in this study used the classical assumption test and hypothesis testing using multiple linear regression, determination test, t test and f test with the SPSS22 program. The results of this study indicate that the work environment has a significant effect on performance. Job stress has no significant effect on performance. Meanwhile, work environment and work stress have a significant effect on employee performance.